2013
DOI: 10.1017/s095026881300143x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic characterization of naturally NS-truncated H3N8 equine influenza virus in South Korea

Abstract: Equine influenza virus (EIV) causes a highly contagious respiratory disease in equids, with confirmed outbreaks in Europe, America, North Africa, and Asia. Although China, Mongolia, and Japan have reported equine influenza outbreaks, Korea has not. Since 2011, we have conducted a routine surveillance programme to detect EIV at domestic stud farms, and isolated H3N8 EIV from horses showing respiratory disease symptoms. Here, we characterized the genetic and biological properties of this novel Korean H3N8 EIV is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…This finding was in accordance with a previously reported in vitro characterization of influenza viruses containing an NS gene segment with a long deletion [24]. Nevertheless, the finding of no difference in growth kinetics between PR8-based recombinant viruses containing NS1 from KYG11 and MA63 in vitro remains controversial because both viruses previously showed notable differences in growth kinetics in MDCK cell culture [2]. Probably, there are mechanisms other than those involving the NS1 protein used to evade the antiviral effects of interferon in cells, and several factors may contribute to the growth efficiency of influenza virus, in particular PR/8, although the NS1 protein is thought to play a significant role in virus replication [22].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding was in accordance with a previously reported in vitro characterization of influenza viruses containing an NS gene segment with a long deletion [24]. Nevertheless, the finding of no difference in growth kinetics between PR8-based recombinant viruses containing NS1 from KYG11 and MA63 in vitro remains controversial because both viruses previously showed notable differences in growth kinetics in MDCK cell culture [2]. Probably, there are mechanisms other than those involving the NS1 protein used to evade the antiviral effects of interferon in cells, and several factors may contribute to the growth efficiency of influenza virus, in particular PR/8, although the NS1 protein is thought to play a significant role in virus replication [22].…”
Section: Discussionsupporting
confidence: 90%
“…There are two distinct influenza A virus subtypes in horses; H7N7 and H3N8. Although H7N7 viruses are no longer circulating in horse populations, H3N8 EIV is continuously isolated in Europe, North America, North Africa, and Asia, including South Korea [1, 2]. It was demonstrated that H3N8 EIV was responsible for the emergence of H3N8 canine influenza A virus (CIV) in North America in 2004 [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Korean H3N8 EIV (strain A/equine/Kyonggi/SA1/2011) was isolated from a horse showing typical symptoms of respiratory disease, and the virus was found to belong to the Florida sublineage clade 1. It is unique that the virus possesses a naturally truncated NS gene segment and shows deduced viral replication in an in vitro kinetic study of growth kinetics (3), which is thought be affected by its NS truncation (4). To study other factors of replication, a sequence analysis of noncoding regions (NCRs) was required, as these regions have multiple functions in the replication of influenza viruses, such as polymerase binding, cap-snatching, transcription initiation, and packaging (58).…”
Section: Genome Announcementmentioning
confidence: 99%